Prevalência de infecçao por leishmania chagasi em cães na ilha do Maranhão, Brasil - FERREIRA, Luiza Costa (2017)
The state of Maranhão is an endemic region for canine visceral leishmaniasis (CVL). The diagnosis is based on specific clinical and laboratory tests, and epidemiological data are also important for diagnostic suspicion. This study carried out a seroepidemiological investigation in the canine population of the Island of Maranhão, and sought to determine and know the regions of higher prevalence for infection in apparently healthy dogs, besides characterizing the clinical and epidemiological profile of the seroreagent animals and to describe the laboratory findings for them. Hemogram, liver enzyme values (ALT), creatinine and total proteins and fractions were used for the laboratory analysis, and for the serological test, the Bio-Manguinhos / FIOCRUZ DPP® rapid test kit was used. The descriptive analysis was done using STATA® and Epi Info® programs, obtaining averages, standard deviations, prevalences and frequencies. 368 animals were screened, of which 114 were reagents; the seroprevalence found was 31% for the Island. Among the municipalities, Paço do Lumiar presented the highest prevalence for CVL, 56.1% and São Luís the lowest, with 13.9%; for the clinical and epidemiological profile, the majority of the animals were male (70.29%), undefined (97.29%), aged six to twelve months (37%), weighing between 11 and 20 kg (62.37%). Most did not wear anti-flea paste; 28.72% presented ectoparasites; 62.38% presented fever and 69.38% were considered asymptomatic. Regarding laboratory analysis, anemia was the most important finding. The laboratory analyzes are complementary to the diagnosis of the disease; anemia in dogs living in endemic areas should lead to the suspicion of CVL. The results also indicate an intense transmission situation in the Island of Maranhão and absence of effective actions to control the disease